Intracellular hydroxyproline imprinting following resolution of bleomycin-induced pulmonary fibrosis. Issue 5 (5th May 2022) - Song, Shengren; Fu, Zhenli; Guan, Ruijuan; Zhao, Jie; Yang, Penghui; Li, Yang; Yin, Hang; Lai, Yunxin; Gong, Gencheng; Zhao, Simin; Yu, Jiangtian; Peng, Xiaomin; et al.
Background: Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease with few treatment options. The poor success in developing anti-IPF strategies has impelled researchers to reconsider the importance of the choice of animal model and assessment methodologies. Currently, it is still not settled whether the bleomycin-induced lung fibrosis mouse model finally returns to resolution. Methods: This study aimed to follow the dynamic fibrotic features of bleomycin-treated mouse lungs over extended durations through a combination of the latest technologies (micro-computed tomography imaging and histological detection of degraded collagens) and traditional methods. In addition, we also applied immunohistochemistry to explore the distribution of all hydroxyproline-containing molecules. Results: As determined by classical biochemical methods, total lung hydroxyproline contents reached a peak at 4 weeks after bleomycin injury and maintained a steady high level thereafter until the end of the experiments (16 weeks). This result seemed to partially contradict with the changes of other fibrosis evaluation parameters, which indicated a gradual degradation of collagens and a recovery of lung aeration after the fibrosis peak. This inconsistency was well reconciled by our data from immunostaining against hydroxyproline and fluorescent peptide staining against degraded collagen, together showing large amounts of hydroxyproline-rich degraded collagen fragments detained and enriched within the intracellular regions at 10 or 16 weeks rather than at 4 weeks after bleomycin treatment. Conclusions: Our present data not only offer respiratory researchers a new perspective towards the resolution nature of mouse lung fibrosis, but also remind them to be cautious when using the hydroxyproline content assay to evaluate the severity of fibrosis. The self-resolving nature of the best-accepted model for lung fibrosis is well reflected by several improved methods but fails to be monitored by classical hydroxyproline assay, emphasising the need to use assessment methods suited to the disease window https://bit.ly/3AsJzSL